Should it be an old wives’ tale? Sexist language awareness amongst UiTM students / Syazliyati Ibrahim ...[et al.] - Ibrahim, Syazliyati; Mohammed, Syakirah; Mohd Nasir, Ida Normaya; Zolhani, Nur Hidyati (Institute of Research Management & Innovation (IRMI), 2013)
Sexism in language has proven to be a viable area for research particularly in the studies of English language because this language is shown to contain sexist elements by various research Sexism in language becomes prominent as a body of scholarship since many research has also proven that the effects of sexism especially on the gender being marginalised due to the language can be detrimental in many aspects like self-esteem and self-respect. In Malaysia so far, studies on sexism have been on analysis of texts and textbooks to highlight the sexist elements. Studies which look at perceived sexism in language especially among the users of the language have not been carried out. Hence, the study seeks to fill the gap by investigating how sexism in language is perceived by the students by measuring their awareness. Three variables which encapsulate awareness which are beliefs about language, ability to identify sexist language and willingness to use sexist language have been chosen as the perimeters in this study. UiTM Kedah students have been chosen as the respondents to this study; focusing on whether the boys or girls are more aware of sexism in language and whether different age groups show any difference in awareness of sexist elements in English language. Findings indicate that there is some awareness (even though not highly significant) of sexism in language, both according to gender and age groups.